Sistem Ujian Tilawatil Qur`an - Muhammad Dedi Irawan; Ali Ikhwan; Oris Krianto Sulaiman; Adi Widarma; Yustria Handika Siregar; Raflikha Aliana A. Raof (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
A group Decision Support System (GDSS) is used when a decision system has many stakeholders providing recommendations in a system. One of them is the Tilawatil of the Qur'an for students in the religious field test. The assessment consists of several raters. The purpose of this study is to apply the SMART (Simple Multi-Attribute Rating Technique) and Borda methods in calculating the results of the Tilawatil Qur'an test based on a decision support system. The SMART method is used in assessing the results of the Tilawatil Qur'an test and the Borda method is used in optimizing the overall results of the assessors on the SMART method. The results of the study were based on the SMART value accuracy test manually with the system yielding 95%. After that, the results of the optimization test of the Borda method were calculated by calculating the average value of the SMART method with optimal ranking results.